Mammary Gland Histological Structure in Relation with Milk Production in Sheep - Mirela Cadar; Vioara Mireşan; Augusta Lujerdean; Camelia Răducu (Scientific Papers Animal Science and Biotechnologies, 2023)
There were collected samples of mammary gland tissue from Ţurcana breed sheep, nearly aged, in lactation stage and with similar mammary gland volume/conformation. By histological and stereological evaluation were determined the relative areas of glandular parenchyma (mammary alveoli, excretion canaliculli system) and stroma (connective tissue, blood vessels, nerves). Before histological sample collecting was determined the average milk production resulted from three successive milking days.